2012
DOI: 10.3791/4022
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an Immortalized Murine Brain Microvascular Endothelial Cell Line as an <em>In Vitro</em> Blood Brain Barrier Model

Abstract: Epithelial and endothelial cells (EC) are building paracellular barriers which protect the tissue from the external and internal environment. The blood-brain barrier (BBB) consisting of EC, astrocyte end-feet, pericytes and the basal membrane is responsible for the protection and homeostasis of the brain parenchyma. In vitro BBB models are common tools to study the structure and function of the BBB at the cellular level. A considerable number of different in vitro BBB models have been established for research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 29 publications
(36 reference statements)
1
39
0
Order By: Relevance
“…iBECs were isolated from Sprague Dawley rats using a previously established method [27] (see ESM Methods ‘Harvest of iBECs’). iBECs were 98% CD31+ by flow cytometry, expressed claudin-5, and had increased phosphorylated Akt in response to insulin stimulation (see ESM Methods ‘Flow cytometry’ and ‘Immunofluorescence’, ESM Fig.…”
Section: Methodsmentioning
confidence: 99%
“…iBECs were isolated from Sprague Dawley rats using a previously established method [27] (see ESM Methods ‘Harvest of iBECs’). iBECs were 98% CD31+ by flow cytometry, expressed claudin-5, and had increased phosphorylated Akt in response to insulin stimulation (see ESM Methods ‘Flow cytometry’ and ‘Immunofluorescence’, ESM Fig.…”
Section: Methodsmentioning
confidence: 99%
“…In an interesting breakthrough, Förster et al ( 2005 ) returned to the earlier cell transduction technology used for bEND3 and bEND5 to generate mouse cEND cells, which uniquely among immortalized brain endothelial cell lines can produce tight monolayers, with reported TEER up to >800 Ω cm 2 . The details of the immortalization method have been published and the cells have been used for studies on the involvement of glucocorticoids on tight junction regulation, and on hypoxia and multiple sclerosis (Burek et al 2012 ).…”
Section: Comparison Of Immortalized Cell Line Models Createdmentioning
confidence: 99%
“…The depths of the media above and below the Transwell chamber were measured again after culturing for 4 h at 37°C under 5% CO 2 condition. If the difference between the liquids remained at 0.4-0.5 cm, this showed that the cells had formed a positive sense barrier [24][25][26][27] .…”
Section: Liquid Surface Leakage Testmentioning
confidence: 99%